2016
DOI: 10.3847/2041-8205/822/2/l34
|View full text |Cite
|
Sign up to set email alerts
|

Kic 8462852 Faded at an Average Rate of 0.164 ± 0.013 Magnitudes Per Century From 1890 to 1989

Abstract: KIC 8462852 is a completely ordinary F3 main-sequence star, except that the light curve from Kepler shows episodes of unique and inexplicable day-long dips with up to 20% dimming. Here, I provide a light curve of 1338 Johnson B-band magnitudes from 1890 to 1989 taken from archival photographic plates at Harvard. KIC 8462852 displays a secular dimming at an average rate of 0.164 ± 0.013 mag per century. From the early-1890s to the late1980s, KIC 8462852 faded by 0.193 ± 0.030 mag. The decline is not an artifact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 19 publications
4
63
0
Order By: Relevance
“…The results of Schaefer (2016) and Montet & Simon (2016) have generally been assumed to indicate that the brightness of Boyajian's Star is monotonically decreasing with time. While the ASAS-SN measurements are consistent with that picture, the longer time baseline afforded by the ASAS data demonstrates that in fact the star's variability may be more complicated, with multiple slow dimming and brightening episodes over the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of Schaefer (2016) and Montet & Simon (2016) have generally been assumed to indicate that the brightness of Boyajian's Star is monotonically decreasing with time. While the ASAS-SN measurements are consistent with that picture, the longer time baseline afforded by the ASAS data demonstrates that in fact the star's variability may be more complicated, with multiple slow dimming and brightening episodes over the past decade.…”
Section: Discussionmentioning
confidence: 99%
“…Until the recent study by Meng et al (2017), all detections of both the long-term dimming of Boyajian's Star and the brief dips in brightness have relied on photometry in a single band (Schaefer 2016;Montet & Simon 2016). Although we find that the ASAS I-band observations indicate fading as well, the larger uncertainties of those measurements prevent us from confidently detecting any color changes in the star over the past decade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Hippke et al (2016) claim the dimming found by Schaefer (2016) is spurious, the unique longer-term variability was again identified with the Kepler full-frame images, which show that KIC 8462852 underwent secular dimming by a total of 3% during the four-year (2009)(2010)(2011)(2012)(2013) Kepler time baseline (Montet & Simon 2016). More recently, Meng et al (2017) presented over 15 months of space-and ground-based photometry from Swift, Spitzer, and AstroLAB IRIS, showing that this variability continues even today.…”
Section: Introductionmentioning
confidence: 99%